Utilization of Bio-based Monomer Derived from Camelina Oil and Itaconic Acid for the Synthesis of Film-forming Latexes - Kolář, Martin; Honzíček, Jan; Podzimek, Štěpán; Hájek, Martin; Lukeš, Vladimír; Klein, Erik; Kocián, David; Machotová, Jana (Springer Nature, 2025)
The need for the production of synthetic polymers from renewable and sustainable resources also affects the area of emulsion polymerization. The bio-based monomer (BBM) was synthesized from camelina oil (CO) and itaconic acid through transesterification and epoxidation of CO, followed by itaconation, resulting in a blend of methyl esters of CO-originated fatty acids functionalized with reactive methyl itaconate groups. Various amounts of BBM (0−30 wt% of BBM in the total monomer mixture) were copolymerized with standard petroleum-based acrylic monomers (specifically methyl methacrylate, butyl acrylate, and methacrylic acid) using the emulsion polymerization technique to obtain film-forming latexes. Infrared and Raman spectroscopies evidenced the successful incorporation of BBM into the structure of latex polymers. The ultra-high molar mass nanogel fraction was detected by asymmetric flow-field flow fractionation coupled with a multiangle light scattering (AF4-MALS) for the BBM comprising copolymers; the higher the BBM content, the more extensive the nanogel fraction. Cross-linking of latex polymers induced by BBM testified to the reactivity of itaconated functions in emulsion polymerization and provided additional evidence of the copolymerization ability of BBM. The incorporation of BBM also resulted in pendulum hardness and glass transition temperature enhancement (about 11% and 9 °C, respectively, in the case of 30 wt% of BBM content in contrast to 0 wt% of BBM content in the copolymer). Coatings with excellent transparency and gloss were obtained from all latexes regardless of the BBM content used. Slightly increased water repellency (about 7 ° increased water contact angle value) and significantly improved water whitening resistance of the coatings (about 80% decreased water whitening after 1-day long water exposure) were found for coatings comprising 30 wt% of BBM in the copolymer, where the water whitening phenomenon was highly dependent on the BBM content.
Keywords: latex coating; emulsion polymerization; bio-based monomer; itaconic acid; camelina oil; water resistance